L’identité – une quête à travers l’écriture (Dany Laferrière) - Elena-Camelia BIHOLARU (Anadiss, 2015)
Our paper aims at examining the relevance correlations existing between the search for identity and the search for writing in the process of literary creation. The corpus consists of a series of interviews given by the writer Danny Laferrrière, a prominent figure characterised by a peculiar identity who assumes and transgresses multiple forms of belonging to a literary genre. The maverick writer’s polemical position regarding the critical reception of his work brings the fight for identity to the very forefront of the creative process. The goals of literature in XXIst century along with the complex act of becoming a contemporary writer are questioning the linguistic, cultural, social and national legitimacy with regard to the writing process in itself.